Remembering Keith Barnes and the Saudi Project: A Tribute to Keith Barnes (1932–2025) and Recollecting the Saudi Project - Holmes, Jim (Journal of Telecommunications and the Digital Economy, 2025)
Keith Barnes died at age 92 on 3 January 2025.  He devoted his whole working life to PMG and Telecom.  He rose from the ranks in the Queensland State Administration to become Chief Planning Engineer in Telecom Headquarters.  Keith did it his way, but his story is broadly typical of many others who contributed to the great infrastructure-building era of telecommunications in the post-war era.  What is not typical is Keith’s last major assignment, which was to lead the in-country team from Telecom Australia to provide a wide range of professional advice and support to Saudi Telecom.  The assignment was unique, big and challenging.  In this article the authors pay tribute to Keith and the team, and reflect upon the Saudi project itself.